2013
DOI: 10.1111/ibi.12118
|View full text |Cite
|
Sign up to set email alerts
|

The decline ofAfro‐Palaearctic migrants and an assessment of potential causes

Abstract: There is compelling evidence that Afro-Palaearctic (A-P) migrant bird populations have declined in Europe in recent decades, often to a greater degree than resident or shortdistance migrants. There appear to have been two phases of decline. The first in the 1960s-1970s, and in some cases into the early 1980s, largely affected species wintering predominantly in the arid Sahelian zone, and the second since the 1980s has mostly affected species wintering in the humid tropics and Guinea forest zone. Potential driv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
413
3
15

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 349 publications
(449 citation statements)
references
References 169 publications
7
413
3
15
Order By: Relevance
“…Bächler et al, 2010;Catry et al, 2011;Akesson et al, 2012;Bairlein et al, 2012;Kristensen et al, 2013) and satellite tracking [Geo Location Sensor (GLS), Eraud et al, 2013;López-López, 2016;Lormee et al, 2016)], are now used for tracking Afro-Palearctic migratory birds, including Turtledoves (Eraud et al, 2013;Lormee et al, 2016). Application of these emerging tracking technologies to North African Turtle-doves would help identify their migratory pathways and strategies (Vickery et al, 2014).…”
Section: Demographic Researchmentioning
confidence: 99%
See 1 more Smart Citation
“…Bächler et al, 2010;Catry et al, 2011;Akesson et al, 2012;Bairlein et al, 2012;Kristensen et al, 2013) and satellite tracking [Geo Location Sensor (GLS), Eraud et al, 2013;López-López, 2016;Lormee et al, 2016)], are now used for tracking Afro-Palearctic migratory birds, including Turtledoves (Eraud et al, 2013;Lormee et al, 2016). Application of these emerging tracking technologies to North African Turtle-doves would help identify their migratory pathways and strategies (Vickery et al, 2014).…”
Section: Demographic Researchmentioning
confidence: 99%
“…Birds have been the focus of intensive research because declines in Palearctic-African migrants have been recorded throughout the Palearctic (Sanderson et al, 2006;European Bird Census Council, 2012;Vickery et al, 2014). The effective conservation of this group poses a particular challenge since migratory birds exploit geographically distinct habitats throughout the annual cycle, including different refuelling sites along migratory corridors.…”
Section: Introductionmentioning
confidence: 99%
“…For example, studies of two populations of Reed Warblers from central Europe (Schaefer et al 2006;Halupka et al 2008) revealed that increased temperatures observed in recent years during the breeding season were correlated with a higher number of nestlings produced by breeding pairs. However, as various recent estimations of population trends for the Reed Warbler have produced equivocal results (Ockendon et al 2012(Ockendon et al , 2014Vickery et al 2014, Inger et al 2015, further detailed studies are needed.…”
Section: Discussionmentioning
confidence: 99%
“…Recent analyses suggest that Reed Warbler numbers are declining in Europe (Vickery et al 2014, but see Ockendon et al 2014;Inger et al 2015). demonstrated that Reed Warbler populations breeding in neighbouring areas of Europe tend to undertake similar migration routes and have wintering grounds in the same parts of Africa.…”
Section: Study Speciesmentioning
confidence: 99%
“…Describing the spatio-temporal distribution of migrant bird populations at all ages and throughout their annual cycle is particularly pertinent given their widespread decline (Sanderson et al 2006;Vickery et al 2013). In particular, understanding the processes by which naïve first-year migrants navigate to and from their first winter site [to which they will usually return with high fidelity in subsequent years (e.g. ]…”
Section: Introductionmentioning
confidence: 99%